An improved computation scheme of strapdown inertial navigation system using rotation technique - Zhang, Lun-dong; Lian, Jun-xiang; Wu, Mei-ping; Hu, Xiao-ping (Journal of Central South University, 2012)
To improve the accuracy of strapdown inertial navigation system (SINS) for long term applications, the rotation technique is employed to modulate the errors of the inertial sensors into periodically varied signals, and, as a result, to suppress the divergence of SINS errors. However, the errors of rotation platform will be introduced into SINS and might affect the final navigation accuracy. Considering the disadvantages of the conventional navigation computation scheme, an improved computation scheme of the SINS using rotation technique is proposed which can reduce the effects of the rotation platform errors. And, the error characteristics of the SINS with this navigation computation scheme are analyzed. Theoretical analysis, simulations and real test results show that the proposed navigation computation scheme outperforms the conventional navigation computation scheme, meanwhile reduces the requirement to the measurement accuracy of rotation angles.